Comparative Study on Soil Infiltration Characteristics of Different Land Use Types in Horqin Sandy Land - Yin Jiawang; Ala Musa; Su Yuhang; Jiang Shaoyan (Shuitu baochi tongbao)
[Objective] The differences in water infiltration characteristics between different land use types in Horqin sandy land were determined in order to provide a scientific reference for the study of water and material transport in the vadose zone in arid and semi-arid regions. [Methods] Soil infiltration and its influencing factors for eight typical land use types (Pinus sylvestris plantation, Caragana korshinsk plantation, Caragana microphylla plantation, abandoned grassland, meadow grassland, sparse forest grassland, corn field, and bare sandy land) in Horqin sandy land were measured in the field using a double ring infiltration apparatus and a laboratory analysis of soil physical properties. At the same time, the Kastiakov model, the Horton model, the Philip model, and the G-P comprehensive model were used to simulate the water infiltration process, and goodness of fit values for the models were compared. [Results] ① There were significant differences in soil infiltration characteristics among different land use types. The initial infiltration rates ranged from 1.595 mm/min to 12.020 mm/min, and followed the order of bare sandy land>Caragana korshinskii plantation>corn field > Pinus sylvestris plantation>Caragana microphylla plantation>meadow grassland>abandoned grassland>sparse forest grassland. The infiltration rate at 15 min varied from 0.617 mm/min to 3.690 mm/min, and followed the order of bare sandy land>Caragana korshinskii plantation>Pinus sylvestris plantation>Caragana microphylla plantation>corn field>abandoned grassland>meadow grassland>sparse forest grassland. The saturated infiltration rate varied from 0.576 mm/min to 3.495 mm/min, and followed the order of bare sandy land>Caragana korshinskii plantation>corn field>Caragana microphylla plantation>Pinus sylvestris plantation>abandoned grassland>meadow grassland>sparse forest grassland. ② The infiltration rate of different land use types was negatively correlated with soil bulk density and fine sand content, and positively correlated with medium sand content. Stable infiltration rate was positively correlated with non-capillary porosity. ③ The goodness of fit values for the models to estimate soil infiltration in Horqin sandy land followed the order of Horton model>G-P comprehensive model>Kastiakov model>Philip model. The Horton model had the highest coefficient of determination and the smallest relative error, and could accurately reflect the actual situation of soil infiltration in Horqin sandy land. [Conclusion] The characteristics of soil infiltration were different among different land use types in Horqin sandy land. The Horton model had high fitting ability in Horqin sandy land, and can, therefore, be used to estimate water infiltration.